Hip Abductor Power and Velocity: Reliability and Association With Physical Function. Issue 2 (23rd February 2023) - Lanza, Marcel B.; Kang, Jin H.; Karl, Hayley; Myers, Jacob; Ryan, Erin; Gray, Vicki L.
Abstract: Lanza, MB, Jin, KH, Karl, H, Myers, J, Ryan, E, and Gray, VL. Hip abductor power and velocity: reliability and association with physical function. J Strength Cond Res 37(2): 284–290, 2023—Muscle power, defined as the ability of the muscle to produce torque quickly, has received little attention and may be critical for understanding physical function and performance. Hip abductors' capacity to produce power through both torque and velocity is important for different human activities; hence, a reliable assessment of hip abduction is critical. The first aim of the study was to assess the intersession reliability of hip abductor muscles maximal torque and submaximal power and power during standing hip abduction in young adults using pneumatic resistance. A secondary aim was to investigate whether there was a relationship between hip abductor maximal torque and submaximal power and velocity with clinical assessments of strength and power in young adults. The subjects ( n = 24; 26.0 ± 3.7 years) visited the laboratory 2 times. In the first visit, the subjects performed on a pneumatic resistance machine 1-repetition maximum (1RM) and submaximal tests (40, 60, and 70% of 1RM) of the hip abductors and clinical tests of lower-extremity strength and power (The 30-second chair stand test [30CST]; and stair climb power test). During the second visit, all tests were repeated except the clinical tests. One-repetition maximum torque and submaximal power and velocity (at all levels) had excellent reliability (intraclass correlation coefficient ≥ 0.943) with absolute reliability of 13.5% up to 28.3%. The agreement between days from Bland-Altman plots for power and velocity was near 0 for all levels. Hip abduction velocity had a significant positive correlation with 30CST at 60% ( r = 0.416; p = 0.048) and 70% of 1RM ( r = 0.442; p = 0.035). In conclusion, we showed an excellent intersession reliability of the hip abductor muscles 1RM torque and submaximal power and velocity using pneumatic resistance. Furthermore, we demonstrated that hip abduction velocity might be important for the performance of the 30CST.